Analysis of motivation, competence and remuneration on employee performance through job satisfaction at PT XYZ cargo area - Marlita, Devi; Dianingrum, Melia; Handayani, Sinai; Perwitasari, Erni Pratiwi; Liana, Esti (Goodwood Publishing, 2025)
Purpose: The purpose of this study was to see the effect of motivation, competence, and remuneration on employee performance through job satisfaction at PT XYZ cargo division. Research Methodology: The method used in this study was descriptive quantitative. The sample consisted of 86 employees. Census was used as the sampling technique. Primary and secondary data were used in this study. The analysis tool used in this study was SmartPLS. The tests carried out in this study included the Validity Test, Reliability Test, Inner Model Test, Outer Model Test, and Hypothesis Test. Results: The results of the research conducted at PT XYZ in the cargo sector include the following: 1) Motivation has a positive and significant effect on job satisfaction; 2) Competence has a positive and significant effect on job satisfaction; 3) Remuneration has no positive and insignificant effect on job satisfaction; 4) Motivation has a positive and significant effect on employee performance; 5) Competence has a positive and significant effect on employee performance; 6) Remuneration has no positive and insignificant effect on employee performance; 7) Job satisfaction has a positive and significant effect on employee performance; 8) Motivation has a positive and significant effect on employee performance through job satisfaction; 9) Competence has a ,positive and significant effect on employee performance through job satisfaction; and 10) Remuneration has no positive and insignificant effect on employee performance through job satisfaction. Conclusions: The study at PT XYZ (cargo sector) concludes that motivation and competence significantly and positively affect both job satisfaction and employee performance, both directly and through job satisfaction. In contrast, remuneration shows no significant positive effect on job satisfaction or employee performance, either directly or indirectly. Limitations: This study's focus on specific companies limits generalizability, and potential bias may arise from self-reported data. Its cross-sectional design restricts causal inferences. Future studies should consider mixed methods to obtain deeper insights. Contribution: This study contributes to the understanding of employee performance and job satisfaction in cargo companies, with a focus on motivation, competence, and remuneration factors.